Oral cancer preventive potential of Polydatin: A nanoencapsulation approach - Sankaran, Vijayalakshmi; Murali, Santhosh Kumar; Ghidan, Alaa; Antary, Tawfiq Al; David, Ernest (Journal of Phytology, 2020)
Over the period, several medicinal plants are recognized as attractive sources of anti-cancer molecules. About 35,000 plant organisms have been tested for possible anticancer activities by the National Cancer Center (NCI). Among them, reproducible anticancer behavior has been shown by around 3,000 plant organisms. Based on this information, we aimed to investigate the cancer preventive efficiency of Polydatin encapsulated PLGA nanoparticles (POL-PLGA-NPs) against 7,12 dimethylbenz (a) anthracene (DMBA) induced buccal pouch carcinogenesis by modulating the antioxidants process in male Syrian hamsters. Oral cancer was initiated on left side buccal pouches by applying DMBA (0.5%), (a known potent chemical carcinogen) on alternative days in a week (thrice a week) for a period of 14 weeks to provoke oral cancer. Sequences of oral squamous cell carcinoma are noted to be manifested exhibiting the formation of incidence, size, mass and development of tumor presented as preneoplastic and neoplastic lesions in hamsters oral buccal pouch tissues. At the same time, oral administration of POL-PLGA-NPs (30mg/kg.b.wt.) considerably increased glutathione peroxidase (GPx) and glutathione (GSH) levels in the buccal tissue thereby decreasing lipid peroxidation activity which resulted in neoplasms incidence in buccal tissue of DMBA painted animals. Thus, POL-PLGA-NPs activity seemed to be a potent cancer preventive agent.